KONSEP RIBA DALAM ISLAM - Sulaiman, Sofyan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Islam Indragiri, 2014)
Riba is avery important issue in Islamic finance transactions. It is a fundamenta lconcept. Ribahas clearly forbidden by Allah, even Allah declared war against theeater of usury. But over time, a debate betwee nulama and experts of Islamic economics with liberal Muslim scholars about the meaning and scope of usury. Ulama and the Islamic economists agree that the meaning of usury include interest, sothe interestis forbidden. While the liberal sargue that the meaning of usury does not include interest based on contextual interpretation. So the interest may be made by reason of providing maslahat he lives of Muslims.